(untitled) (Південний архів (історичні науки), 2023)
Purpose – comparison of the situation of children during the Ireland’s Great Hunger (1845–1851) and the Holodomor (1932–1933): threats, survival practices, consequences. Research methods. The method of comparative analysis was used during the research. The main points of comparison were: the mortality rate from hunger and associated diseases and methods of its calculation; consequences of famines – impact of famine on childhood: crisis of family relations, crime and destructive factors; survival practices: survival skills, help, mutual aid; commemorative practices. Adhering to the principle of historicism, the context of historical eras against which the events of the Great Famine in Ireland and the Holodomor in Ukraine unfolded was investigated. For this, scientific literature covering the events of famines and the topic of childhood during them, archival sources, diaries and memories of eyewitnesses were involved. Research results: a comparative analysis of threats, survival practices, consequences of the Ireland’s Great Hunger (1845–1851) and Holodomor (1932–1933) for children and childhood was carried out. Conclusions. The source base for the study of the Ireland’s Great Hunger of 1845–1851 in Ireland and the Holodomor of 1932–1933 in Ukraine is sufficient, but has the potential for development: the identification of new sources, in particular oral history and archeology, the continuation of public involvement in the collection of memories, the formation of electronic databases data and museum exhibits. These measures will help to simultaneously identify new sources and preserve the memory of famines. It was found that the common features were the silence of the famine by its organizers – the governments of Great Britain and the USSR, respectively, which led to the death of a significant number of the population, among which the most vulnerable and the most numerous category of victims were children, as well as the attempts of these colonial states to blame the Irish and Ukrainian peoples for the famine, to justify inhumane policies; the increase in the number of homeless and neglected children due to the fact that their parents leave their children behind when they go to America, Australia (Ireland) and Donbas, Crimea (Ukraine) to earn money. Although it is forbidden for Ukrainians to leave their settlements at this time, this did not stop migration, it only created new risks. A special feature of the Ukrainian realities of the 1930s is the orphan hood of children as a result of repression against their parents, but labor emigration, the basic principles of the workhouses in Ireland also have signs of repression directed against the Irish population, consisting of national and social discrimination, the destruction of the family, hardly, since it is not even possible to talk about the “voluntariness” of the choice in conditions of famine. During the famines in Ireland and Ukraine, a humanitarian crisis is observed. In Ukraine, there are cases of infanticide and cannibalism, which have not become widespread in Ireland. The peculiarity of the loss of moral landmarks lies in the Soviet anti-religious campaign, but if the Irish had at least spiritual consolation in the support of the church, the fate of children who ended up in workhouses was little different from the fate of Ukrainian children who fell under the care of orphanages. It was these institutions that literally became the last refuge for many children. The hopeless situation leads to the cruel exploitation of child labor and the spread of crimes against children, the growth of child crime. A special feature of Soviet social policy was the destruction of family values: children were used to organize famines, and they were called to report on their parents. A common feature was the inability of parents to protect their children in conditions of famine and preserve family relations. We can talk about the importance of not only material, but also moral assistance to children and families who find themselves in difficult situations.